1983
DOI: 10.1104/pp.73.4.1038
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of Oxygen in Mesophyll Chloroplasts of C4 Plants

Abstract: Mesophyll chloroplasts of three C4 sub types, Panicum miliaccum (NAD-malic enzyme), Panicum maximum (PCK), and Zea mays (NADPmalic enzyme), were prepared from protoplast extracts and used to study the photoreduction of 02. The processes of 02 uptake and evolution in these preparations, which lack ribulose 1,5-bisphosphate carboxylase/ oxygenase, were studied simultaneously using stable isotopes of 02 and mass spectrometry. The responses of 02 uptake to 02 tension and addition of various substrates (3-phosphogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Furthermore, with 02 concentrations exceeding 20%, net photosynthesis was 02 insensitive although it was very CO2 sensitive; also, 02 uptake was 02 insensitive, weakly CO2 sensitive, and never inhibited by high CO2 concentration, contrary to theoretical predictions of such conditions (2). All (16,18). The affinity for 02 of 02 uptake observed in C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, with 02 concentrations exceeding 20%, net photosynthesis was 02 insensitive although it was very CO2 sensitive; also, 02 uptake was 02 insensitive, weakly CO2 sensitive, and never inhibited by high CO2 concentration, contrary to theoretical predictions of such conditions (2). All (16,18). The affinity for 02 of 02 uptake observed in C.…”
Section: Resultsmentioning
confidence: 99%
“…But also, these discrepancies suggest that: (a) the Rubisco enzyme differs either as it is isolated or placed in its functional cellular environment; or (b) the Rubisco enzyme is not involved in all of the 02 photoconsumption. From several reports on higher plants (2,(16)(17)(18)25) and microalgae (7,11,15,21,26,(28)(29)(30) organisms. Furthermore, some microalgae have presented gas exchange kinetics in contradiction with the expected competition between 02 and CO2 at the Rubisco enzyme level for photochemically generated reducing equivalents (15,29,30), and exhibit no detectable photorespiration as measured by CO2 release in the light (24,30).…”
Section: Abstracimentioning
confidence: 99%
See 1 more Smart Citation
“…McVetty and Canvin (1981) suggested that pseudocyclic photophosphorylation may be decreased at low p(O 2 ). Pseudocyclic phosphorylation due to photoreduction of oxygen has been shown to be necessary for balancing ATP and NADPH requirements in mesophyll chloroplasts of C 4 -plants (Furbank, Badger, and Osmond, 1983). No pseudocyclic electron flow can occur in the absence of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…John Andrews and Murray Badger predicted and proved that C 4 RuBisCO would show higher K m for CO 2 (9), Paul Hattersley pioneered immunofluorescent localization of both carboxylases (53) (42). Tom Neales and I were determined to put CAM into the picture of the prickly pear (Opuntia inermis/stricta) invasion of eastern Australia (1846-1933), otherwise remembered only for the success of biological control (114,128).…”
Section: Head Of the Department Of Environmental Biology: 1978-1983mentioning
confidence: 99%